Dinâmica espaço-temporal da raiva animal e bioecologia de quirópteros na microrregião de Porangatu, Goiás, Brasil - TOMAZ, Leonardo Aparecido Guimarães (2009)
Rabies is viral lethal encephalitis that causes annual spoil of hundreds million dollars to the livestock and the public health. Starting from the 90 s bats became the main transmitters of this zoonose in Brazil. In spite of the unquestionable participation of these encourage in the transmission of the illness, studies that it relate them to the distribution of the animal rage are still scarce. In this context, the present paper aimed at to study epidemiologic aspects related to the aerial cycle of the rabies and it space-temporal development in the Porangatu s microregion of through bats capture in natural and artificial shelters from Niquelândia and Barro Alto; besides the analysis of the results for rabies laboratorial exams (IFD and ICC) in the nineteen municipal districts in the historical series 1999 -2008. From May of 2007 to April of 2008 four expeditions were accomplished to four Cerrado ranches in the two cities with 402 bats captured in eleven natural and artificial shelters. Desmodus rotundus was the single hematophagous species captured and just found at grottos in the Barro Alto municipal district. Their colonies were composed predominantly by females. The sexual reason between males and females was of 1:1,43 and the largest number of pregnant concentrated on the rainy period. Five species were found sharing shelter of D. rotundus. The chiropterofauna was shown quite several, with prevalence of frugivorous species. The rabies space-temporal analysis in the microregion demonstrated the disease was hight or smaller intensity diagnosed in all of the municipal districts. The number of samples sent for laboratory oscillated during the historical series with tendency of accumulation of positive results in the month of November. The results indicated although and that the surveillance of the rabies needs to be intensified in the whole microregion